2013
DOI: 10.1111/jpim.12047
|View full text |Cite
|
Sign up to set email alerts
|

Patenting Activities and Firm Performance: Does Firm Size Matter?

Abstract: Whereas prior research has provided valuable insights into the willingness of small and medium‐sized enterprises (SMEs) and large firms to engage in patenting, a comparison of the performance implications of patenting activities across small and large firms is still lacking. This gap is important because SMEs and large firms, having different resources and capabilities, might benefit from patenting activities in different ways. In particular, SMEs can be expected to benefit less from patenting activities in te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(91 citation statements)
references
References 49 publications
3
77
2
2
Order By: Relevance
“…Consistent with past research indicating that the effect of entrepreneurial and sustainable activities on performance may be contingent on firm size and age (Andries and Faems 2013;Aragon-Correa et al 2008), we controlled for both variables. Firm size was measured by a proxy, namely, the number of full-time equivalent employees who were employed over the last year (1-9, 10-19, 20-49, 50-99, 100-199, and 200-249).…”
Section: Control Variablesmentioning
confidence: 87%
“…Consistent with past research indicating that the effect of entrepreneurial and sustainable activities on performance may be contingent on firm size and age (Andries and Faems 2013;Aragon-Correa et al 2008), we controlled for both variables. Firm size was measured by a proxy, namely, the number of full-time equivalent employees who were employed over the last year (1-9, 10-19, 20-49, 50-99, 100-199, and 200-249).…”
Section: Control Variablesmentioning
confidence: 87%
“…Abouzeedan et al (2013) argue that these challenges include scarcity of resources, complexity of scientific field, coordination of the operative functions of the firm, and access to up-to-date scientific excellence. Even though licensing out the knowledge of SMEs to external parties is beneficial for them, it is not appropriate for short-term benefits (Andries and Faems 2013). Christensen et al (2005) highlighted that the complexity of interplay between technology entrepreneurs and incumbents.…”
Section: Challenges For Innovation Managementmentioning
confidence: 99%
“…Andries and Faems (2013) found that patenting activities significantly help SMEs to license out their knowledge to external parties. Timely recognition of opportunities for out-licensing a firm's technologies outside its core business is challenging.…”
Section: Patentingmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we incorporated a dummy variable to distinguish high-tech SMEs from non-high-tech SMEs (e.g. Andries and Faems, 2013) by drawing on Eurostat's (2014) NACE Rev. 2 distinction between high-tech or knowledge-intensive sectors and non-high-tech or non-knowledge-intensive sectors (see Table 3).…”
Section: Robustness Checksmentioning
confidence: 99%